Where do people tweet? The relationship of the built environment to tweeting in Chicago. (January 2020) - Chen, Yan; Song, Yan; Li, Chaosu
Highlights: A new framework to study the relationship between built environment and social media behavior. A replicable method to collecting and analyzing social media activity data across a large spatial area 400 thousands tweet in Chicago are collected to examined the activity pattern Interaction effect between each built environment factors plays a vital role for social media activity The residential density serve as a negative factor for social media activity after controlled its interaction effect Abstract: Understanding the relationships between human activities and the built environment are central to urban planning. The increase in readily available, location-based social media data offers scholars important new data for understanding this relationship. This study examines the relationship between the spatial distribution of geotagged tweets and key characteristics of the built environment at the census block group level in Chicago. First, we performed a hotspot analysis to ascertain the distribution of tweets in the study area. Then, we employed a count regression model with Twitter message counts by census block group as the dependent variable to test the significance and magnitude of the associations between the built environment and tweeting. After that, we standardized the coefficients to compare the variables' effects on tweeting. The analysis found that the built environment significantly influenced tweeting and provides empirical statistical evidence to guide urban planners' placemaking decisions.